PERSONAL INFORMATION ARCHIVING: BEHAVIOURAL RESPONSES TO THE PERCEPTION OF RISK - Lin, Chang; Jacobson, Jenna; McEwen, Rhonda (AoIR Selected Papers of Internet Research, 2019)
The paper investigates the factors that influence perceptions of online risk and the consequential behavioural responses to those perceptions. Using Bates’ theory of information behaviour, we focus on online protection strategies and digital archiving as a specific instantiation and manifestation of information behaviour and analyze how factors, such as perceptions of online risk and self-reported internet skills, have consequences for information behaviours. The study uses semi-structured interview data (n=101) collected from East York, Toronto. We asked about individuals’ perception of risk online, self-reported internet skills, protective measures when going online, and digital archiving practices. Our findings identify a nuanced relationship between perceptions and behaviours. The results offer an alternate perspective on online information behaviour that departs from traditional classifications that rely on _demographics_. We offer a refinement to the definitions of information behaviour by Bates (2010) and Fisher and Julien (2009) to include factors that modify behaviours, and develop a user typology relating specifically to perceptions of risk online.